DESIGNING A COMPUTER SYSTEM FOR REMOTE OFFICES: TRADITIONAL SYSTEM VERSUS CLOUD SYSTEM Case: Church council of the Evangelical Lutheran church of Finland - Niskanen, Sami (My University, 2012)
This thesis is about a comparison between two models for building a system, a traditional model versus cloud model. The thesis looks through the framework which is the history, present day and the future of the It in the church and the Church Council. It also takes a look at the history, the present day, security threats and costs of the systems. The type of this study is constructive. There was a lot of material in use. A major part of the material was found through the university’s Nelli database search and the material and references describe and support the thesis well. There are also thoughts and facts about the information technology in the church, rising from the writer’s own experience. Valuable help was also received via an interview from the manager of the ICT-Management Unit, and also from partners who are in cooperation with the church. Despite being the most talked about subject in the IT world, there was not much generally scientific information about cloud services, only some researches covering a small specific area. For example, defining the costs of the service was difficult. However, there are some pricing models introduced in this paper. The conclusion was that given the present information, it is more reasonable to build the system the traditional way. The reasons for this are the resources in use, the know-how of the users and the IT personnel and the variance of the cost of the cloud services
Keywords: Cloud; service; system; design; remote office; fi=Tietotekniikka (KTM)|en=Computer Science|